Marketing Strategy In An Islamic Economic Perspective (Study On The Uliq Food Kudus) - Nur Hikmah; Muhammad Ali Subkan; Purwati Purwati (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
The aim of writing this research is to find out the marketing strategy, the advantages and disadvantages of the marketing strategy, and the implementation of the marketing strategy for Uliq Food Pedawang Kudus from an Islamic economic perspective. Apart from theory, marketing strategies need to be applied in the real business world. Whether successful or not, marketing strategies can be a place for future evaluation. Descriptive qualitative methods were used as instruments in discussing this research. Observations and interview techniques will support this research. The theoretical basis of marketing strategy formulates a thought to be applied in all the company's economic activities in order to achieve the company's goals and for the company's survival. The research results show that Uliq Food's marketing strategy broadly includes four aspects, namely product strategy, price strategy, promotion strategy and distribution strategy. Overall the marketing strategy aims to increase sales results and increase profits. Uliq Food's marketing strategy from an Islamic economic perspective is based on the belief that owners as humans must run businesses in accordance with Islamic principles. The Islamic economic attitude that underlies Uliq Food's marketing strategy includes an ethical, realistic and humanistic attitude.